COMPARING OF IRAN AND TURKEY’S MANAGEMENT CULTURE DEPENDING ON FEMANIN/MASCULINE DIMENSION OF HOFSTEDE (Third Sector Social Economic Review, 2014)
In this paper, Iran and Turkey’s Management Culture has been compared, using masculine and femenine size, and existed Hofstede culture size. The research has been done on 200 students with Iranian and Turkish natinality and who are studying in universities of Ankara city included Gazi, Hacettepe and Ankara universities. To make the survey admissible, we selected same ratio of Iranian and Turkish students and same ratio of male and female students. In this research, we used questionnair method. We analysis collected data using SPSS program. In given analysis One sample t-Test analysis, Independent Sample t-Test and Correlation Analysis have been used. According to findings in the research, in Iranian and Turkish societies at Hofstede dependance “Femininity” level in dominante. Besides, In Iranian and Turkish society level of “Femininity / Masculinity” and “Management Culture” has relation. Finally in this research, it has been discovered that in Iran and Turkey’s level of “Femininity / Masculinity” and “Management Culture” are not different.
Keywords: Masculine; Feminine; Management Culture; Cultural Differences